Evaluasi sistem pengendalian internal, transparansi dan akuntabilitas dalam pengelolaan dana desa (Studi kasus di Desa Pulutan Utara, Kecamatan Pulutan, Kabupaten Kepulauan Talaud) - Cristiano Sumare; Jantje J. Tinangon; Wulan D. Kindangen (Riset Akuntansi dan Portofolio Investasi, 2026)
Accountable and transparent village fund management is a primary pillar of good village governance; however, its practice is often hindered by weak supervision systems and limited access to public information. This study aims to evaluate the effectiveness of the Internal Control System (ICS), transparency, and accountability in managing Village Funds in Pulutan Utara Village. Employing a descriptive qualitative method with a case study approach, data were collected through in-depth interviews and observations involving village officials and the community. The results indicate that the ICS has operated effectively structurally and administratively based on the five elements of the Government Internal Control System; yet, its function as social control remains suboptimal due to a lack of community involvement. Fund management accountability has performed well vertically towards the local government, but horizontal accountability to the community is still highly limited. Similarly, transparency functions adequately in a formal sense through village deliberations, but sustainable information accessibility remains weak due to the minimal use of written and digital media. This study implies that the fulfillment of administrative (vertical) obligations must be balanced with innovations in public information disclosure to realize substantive community participation in preventing potential deviations.